2015
DOI: 10.1097/shk.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Full Activation of CD4+ T Cells Early During Sepsis Requires Specific Antigen

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
(81 reference statements)
1
13
0
1
Order By: Relevance
“…This model mimicked septic complications in abdominal surgical patients in which preventive use of an ω‐3 PUFA‐enriched enteral formula may be recommended. We evaluated the outcomes 1 and 3 days after CLP because it will take more than 1 day of newly formed antigen‐specific T cells to proliferate, differentiate, and become mature lymphocytes in the circulation 14 . In this study, we found that the diet supplemented with fish oil had some favorable effects on aspects of CD4+ cell modulation and the inflammatory response that were not observed with the soybean oil–based diet.…”
Section: Discussionmentioning
confidence: 99%
“…This model mimicked septic complications in abdominal surgical patients in which preventive use of an ω‐3 PUFA‐enriched enteral formula may be recommended. We evaluated the outcomes 1 and 3 days after CLP because it will take more than 1 day of newly formed antigen‐specific T cells to proliferate, differentiate, and become mature lymphocytes in the circulation 14 . In this study, we found that the diet supplemented with fish oil had some favorable effects on aspects of CD4+ cell modulation and the inflammatory response that were not observed with the soybean oil–based diet.…”
Section: Discussionmentioning
confidence: 99%
“…The missing concept in the current understanding of the dynamics of the therapy of infectious diseases is that the success of antimicrobial drugs is ultimately dependent on the underlying immune response: antimicrobials are often necessary but never sufficient without a proper immune response. This conceptual mistake is probably responsible for the virtual absence of effective treatments for sepsis, septic shock, and severe infections and for the countless clinical trial failures of medicines that were promising in preclinical studies (7,8,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…stimulation with specific antigen (Schmoeckel et al, 2015). Thus, an incomplete/partial stimulation of CD4 + T and CD8 + T cells during sepsis in a T-cell receptor (TCR)-independent manner may cause their increased apoptosis (Esser et al, 2001).…”
Section: Cd4 + Cd8 + and Cd4 + Cd8 + T Cells In Sepsismentioning
confidence: 99%